The Word Outside and the Pictures in Our Heads: Contingent Framing Effects of Labels on Health Policy Preferences by Political Ideology - Sungjong ROH (Institutional Knowledge at Singapore Management University, 2016)
This study uses data from systematic Web image search results and two randomized survey experiments to analyze how frames commonly used in public debates about health issues, oper- ationalized here as alternative word choices, influence public support for health policy reforms. In Study 1, analyses of Bing (N = 1,719), Google (N = 1,872), and Yahoo Images (N = 1,657) search results suggest that the images returned from the search query “sugar-sweetened beverage” are more likely to evoke health-related concepts than images returned from a search query about “soda.” In contrast, “soda” search queries were more likely to incorporate brand-related concepts than “sugar-sweetened beverage” search queries. In Study 2, participants (N = 206) in a controlled Web experiment rated their support for policies to reduce consumption of these drinks. As expected, strong liberals had more support for policies designed to reduce the consumption of these drinks when the policies referenced “soda” compared to “sugar-sweetened beverage.” To the contrary, items describing these drinks as “soda” produced lower policy support than items describing them as “sugar-sweetened beverage” among strong conservatives. In Study 3, participants (N = 1,000) in a national telephone survey experiment rated their support for a similar set of policies. Results conceptually replicated the previous Web-based experiment, such that strong liberals reported greater support for a penny-per-ounce taxation when labeled “soda” versus “sugar-sweetened beverages.” In both Studies 2 and 3, more respondents referred to brand-related concepts in response to questions about “sugar-sweetened beverages” compared to “soda.” We conclude with a discussion of theoretical and methodological implications for studying framing effects of labels.